Boriding and boronitrocarburising effects on hardness,wear and corrosion behavior of AISI 4130 steel - Nora,Ramdane (2019)
ABSTRACT The effects of boriding and boronitrocarburising surface treatments on the microstructure and mechanical properties of AISI 4130 steel have been investigated. Pack boriding was carried out at 1223 K for 5 h and 8 h, while the double treatment of boronitrocarburising consisted of salt bath nitrocarburising at 853 K for 6 h followed by pack boriding at the same temperature and times as the boriding treatment. Microstructure examination of the borided and boronitrocarburised layers was carried out using optical and scanning electron microscopy, and phase identification was obtained using X-ray diffraction. Vickers hardness, wear and corrosion weight loss tests were used to evaluate the mechanical properties and corrosion behaviour. The results of X-ray diffraction analysis revealed the presence of superhard phases such as FeB, Fe2B, CrB, MnB and MnB2, indicating that pack boriding surface treatment conducted at 1223 K for 8 h exhibited the highest hardness, low coefficient of friction and the greatest wear resistance. Boronitrocarburising treatment, on the other hand, caused a reduction in both the depth of iron borides zone and mechanical properties compared to the boriding surface treatment. These recommended treatments offer to industrialists a particular contribution and interest in the development of these steels, which can be applied in various fields.